Effects of communication strategy training on EFL students’ performance in small-group discussions - Benson, Stuart; Fischer, Danielle; Geluso, Joe; Von Joo, Lucius (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2013)
In recent years, a number of studies have been conducted with regard to communication strategy training and performance on communicative tasks (Lam, 2009; Nakatani, 2010; Naughton, 2006). This study aims to add to the literature by examining how two strategies, clarifying/confirming and ex- tending a conversation, and two methods of teaching the strategies, affect- ed the interactional sequences and overall group discussion performance of EFL students at a university in Japan. Pre and posttreatment small-group discussions were recorded for assessment, and a stimulated recall interview was administered to determine the participants’ perceptions of their learn- ing and language use. Posttest results reveal that the experimental groups that were taught predetermined phrases aimed at clarifying/confirming and extending a conversation employed such phrases more frequently than the control group. However, this employment of phrases did not lead to higher gains in group discussion skills as the control group enjoyed the largest gains from pre to posttest. The researchers consider the findings in light of previ- ous research, and conclude with recommendations for future research on the topic with special regard to research design.
Keywords: English as a foreign language; small-group discussions; communication strategies; explicit instruction; co-constructed learning